A centralized global automation group in a decentralized organization. Issue 6 (2000) - Ormand, James; Bruner, Jimmy; Birkemo, Larry; Hinderliter-Smith, Judy; Veitch, Jeffrey
Abstract : In the latter part of the 1990s, many companies have worked to foster a matrix style culture through several changes in organizational structure. This type of culture facilitates communication and development of new technology across organizational and global boundaries. At Glaxo Wellcome, this matrix culture is reflected in an automation strategy that relies on both centralized and decentralized resources. The Group Development Operations Information Systems Robotics Team is a centralized resource providing development, support, integration, and training in laboratory automation across businesses in the Development organization. The matrix culture still presents challenges with respect to communication and managing the development of technology. A current challenge for our team is to go beyond our recognized role as a technology resource and actually to influence automation strategies across the global Development organization. We shall provide an overview of our role as a centralized resource, our team strategy, examples of current and past successes and failures, and future directions.